Research recast(ed): MacEwan Celebrates Month of Scholarship - Dr. Erin Walton - Ekelund, Brittany; Cave, Dylan; Walton, Erin (My University, 2022)
Today’s episode is literally out of this world as we talk about meteorites, asteroids and moon rocks with geologist Dr. Erin Walton, an associate professor in the Department of Physical Sciences at MacEwan University, whose primary research focuses on shock metamorphism recorded in martian meteorites. Along the way, we’ll discuss mentorship, space colonization and the economic benefit of finding impact craters. We will also get a glimpse into Dr. Walton’s new exciting avenue of research into her all-time favorite asteroid, 4-Vesta.
Keywords: meteorites; space colonization; impact craters